Mosaic PKHD1 in Polycystic Kidneys Caused Aberrant Protein Expression in the Mitochondria and Lysosomes - Xu, Chengxian; Yang, Chenxi; Ye, Qing; Xu, Jie; Tong, Lingxiao; Zhang, Yuchen; Shen, Huijun; Lu, Zhihong; Wang, Jingjing; Lai, Enyin; Mao, Jianhua; Jiang, Pingping (Frontiers in Medicine, 2021)
Autosomal recessive polycystic kidney disease (ARPKD) is a severe renal cystic disease caused mainly by the polycystic kidney and hepatic disease 1 (PKHD1). However, the genetic cause, pathologic features, and mechanism of action of ARPKD are not well known. Here, we identified a family with ARPKD. Two siblings harbored biallelic variants in PKHD1 (c.7205G>A, c.7973T>A). We determined that the “de novo” variant, c.7205G>A, arose from the mosaicism of the father and had a 7.4% level. Pathologic characterization, using biopsy analysis, was evidenced with predominant cystic dilation in proximal tubules, slight ectasia of collecting ducts, defective ciliogenesis, and impaired cell-cell junctions in renal tubules and collecting ducts. Exosome proteomics in the urine from patients with ARPKD were markedly different from those of controls, with the most significant alterations occurring in mitochondrial and lysosomal proteins. Expression of the proteins of OXPHOS was downregulated sharply, in parallel with upregulated expression of the proteins involved in glycolysis in patients with ARPKD. Several lysosomal proteins associated with renal lesions were more abundant in the exosome of the patient than in controls. Moreover, the lysosomal enzyme sulfamidase, which is produced by the SGSH gene, was abrupt uniquely in the exosome of the patient. Consistently, swollen mitochondria and abundant lysosomes were visualized in the mutant tubular epithelial cells of patients with mutant PKHD1. Collectively, these findings provide new insights on the pathophysiology of the polycystic kidney due to PKHD1 deficiency. PKHD1 mosaicism should be considered in genetic testing of ARPKD patients.